T2 Signal Intensity of the Trigeminal Nerve: A New Diagnostic Criteria for Trigeminal Neuralgia? - Kaya, Ozlem K.; Alkan, Alpay; Hatiboglu, Mustafa A.; Timocin, Gizem; Badur, Bahar A.; Bilgin, Mehmet (Current Medical Imaging, 2018)
Objectives: The objectives of this study were to: 1) compare the size and T2 signal intensity of the trigeminal nerves on the symptomatic side and asymptomatic side of the patients with idiopathic trigeminal neuralgia and to correlate these morphological findings with each other in order to assess whether Magnetic Resonance Imaging (MRI) can provide evidence of microstructural changes in the affected trigeminal nerve that could be potential imaging markers for diagnosis and monitoring trigeminal neuralgia 2) correlate these data with the pain score of the patients in order to search a quantitative evaluation method of the pain in patients with Trigeminal Neuralgia (TN). Materials and Methods: The subjects were 18 adults with clinically diagnosed trigeminal neuralgia. We compared the trigeminal nerve size and T2 signal intensity on the symptomatic side and asymptomatic side for each patient via three-dimensional constructive interference in steady-state (3D-CISS) MRI. Then, we correlated these structural changes with pain score of the patients. Results: The mean diameter of the trigeminal nerve on the affected side was significantly smaller than the mean diameter on the unaffected side (p=0.004). The mean T2 signal intensity of the trigeminal nerve on the affected side was significantly higher than the unaffected side (p=0.004). There was a significant negative correlation between T2 signal intensity and diameter of the nerve (p=0.001). However, there was no significant correlation between the nerve atrophy, T2 signal intensity and pain score. Conclusion: On the affected side the size of the trigeminal nerve was smaller and T2 signal intensity of the nerve on the affected side was higher and these two findings strongly correlated with each other. These microstructural changes that defined noninvasively via 3D CISS MRI can provide new insight about the trigeminal neuralgia pathogenesis and also can be useful reliable markers for diagnosis and follow-up of treatment response in TN.
Keywords: pathogenesis